Assessment of mycotoxin exposure and risk characterization using occurrence data in foods and urinary biomarkers in Brazil. (June 2019) - Franco, Larissa T.; Petta, Tânia; Rottinghaus, George E.; Bordin, Keliani; Gomes, Gilmar A.; Alvito, Paula; Assunção, Ricardo; Oliveira, Carlos A.F.
Abstract: This study aimed to assess the exposure of Brazilian residents ( N = 86) from rural areas to multiple mycotoxins and characterize the associated risk in two sampling periods (SP) (April–May and December/2016). Mycotoxins in food and urine samples were determined by liquid chromatography coupled to tandem mass spectrometry. Mean probable daily intake (PDI) values based on occurrence data in foods in both SP varied from 0.007 to 0.013, 0.069 to 1.002, 0.119 to 0.321 and 0.013–0.156 μg kg −1 body weight (bw) day −1 for aflatoxins (AFs), deoxynivalenol (DON), fumonisins (FBs) and zearalenone (ZEN), respectively. Mean PDI values based on urinary biomarkers were 0.001, 84.914, 0.031, 0.377 and 0.002 μg kg −1 bw day −1 for AFB1, DON, ochratoxin A (OTA), FB1 and ZEN, respectively. Hazard quotient (HQ) calculated using food data revealed a potential health concern for ZEN in 2nd SP. HQ > 1 based on urinary biomarkers were observed for DON in the two SP. Although OTA was not detected in any food sample, the HQ based on urinary OTA levels was >1 in the 1st SP. Margin of exposure values for AF from food and urine data in the 1st SP were below 10, 000, indicating potential health risks. Graphical abstract: Image 1 Highlights: Mycotoxin exposure evaluation and risk assessment in rural areas from Brazil. 53% of food samples analyzed ( N = 203) presented at least one type of mycotoxin. Urinary biomarkers of mycotoxins found at levels of 0.02–12.0 ng mg −1 creatinine. PDI based on biomarkers in urine exceed recommended TDI values for DON and OTA. Margin of exposure values indicated health risks associated with dietary aflatoxins.